Letter to the Editors - Gore, C. J.; Hahn, A. A. G. (International Journal of Sports Medicine, 2005)
Kommentar zum Artikel von Heinicke, K.;Heinicke, I.;Schmidt, W.;Wohlfarth, B.A.: Three-week traditional altitude training increases hemoglobin mass and red cell volume in elite biathlon athletes